Replication and incompatibility properties of plasmid pE194 in Bacillus subtilis. - Gryczan, T J (1982)
pE194, a 3.5-kilobase multicopy plasmid, confers resistance to the macrolide-lincosamide-streptogramin B antibiotics in Bacillus subtilis. By molecular cloning and deletion analysis we have identified a replication segment on the physical map of this plasmid, which consists of about 900 to 1,000 base pairs. This segment contains the replication origin. It also specifies a trans-acting function (rep) required for the stable replication of pE194 and a negatively acting copy control function which is the product of the cop gene. The target sites for the rep and cop gene products are also within this region. Two incompatibility determinants have been mapped on the pE194 genome and their properties are described. One (incA) resides within the replication region and may be identical to cop. incB, not located in the replication region, expresses incompatibility toward a copy control mutant (cop-6) but not toward the wild-type replicon.